Fenomena di Hari Kiamat Dalam Al-Qur’ān : (Kajian Analisis Integratif Kebahasaan Dalam Kitab Tafsir Al-Qurtubi) - Fatihatun Nadliroh (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2024)
Doomsday is the culminating event of all life on this earth in the form of the destruction of the universe and all its contents, including human existence. No creature can survive the apocalypse. This phenomenon is explained in several verses of the Koran. Imam Al-Qurt}ubi is of the view that the last day and doomsday will occur if knowledge is revoked, there will be many earthquakes, time will pass very quickly, there will be a lot of slander and chaos and murder will occur everywhere. The aim of this research is to determine the linguistic aspects of the doomsday phenomenon in al-Qurtubi's view. The research method used in this research is library research. The data source was obtained from primary data sources in the form of the Al-Qurt}ubi interpretation book entitled Al-Jamī' Li Al-Ahkam Al-Qur'ān. And primary data sources come from various related literature in the form of books and journals. Data collection techniques use library and documentation techniques. Then the data was analyzed using content analysis. This research resulted in the finding that the linguistic aspects regarding the doomsday phenomenon are known to be dominated by metaphors in the narrow and open sense in several verses of the Qur'an. These two forms of language style both do not mention comparative motifs.